Exploring the adoption of food safety measures in smallholder dairy systems in Ethiopia: implications for food safety and public health - Ndungu S. Nyokabi; Lilian Korir; Johanna F. Lindahl; Lisette Phelan; Gizachew Gemechu; Stefan Berg; Adane Mihret; James L. N. Wood; Henrietta L. Moore (Food Security, 2024)
Abstract Milk is highly perishable and can be a conduit for the transmission of zoonotic foodborne pathogens. This cross-sectional survey involving 159 farming households and 18 participant observations in participating farms was undertaken in Addis Ababa and surrounding areas in Oromia, Ethiopia to assess the adoption of food safety measures in smallholder farms. Adoption of food safety measures at the farm level influences milk quality and safety across the entire milk value chain, from “grass to glass”. This study considered the adoption of 36 different food safety measures (FSM) including animal health, milking hygiene, hygienic milk storage, and hygienic milking premises. A weighted food safety index (FSI, ranging from 0 to 100) was calculated for each household based on FSM adopted. Ordinary Least Squares linear regression was used to quantify the factors of FSM adoption by smallholder farmers. The overall food safety index ranged between 59.97—60.75. A majority of farmers may be classified as moderate adopters of FSM (index ranging between 30–70%). Farm and farmers' characteristics such as herd size, farmer's education level, farmer's expertise in dairying, and participation of the farm in the formal milk value- chain, were shown to positively influence the level of adoption of FSM. Low farm-level adoption of FSM has food safety and public health implications as it can lead to milk contamination and, therefore, expose consumers to foodborne diseases. There is an imperative for policymakers to design and implement policies and intervention strategies that lead to increased farmer training related to livestock production and awareness of the important role that FSM adoption can play in improving food safety and public health.
Keywords: 330; Milk quality; Fresh milk; Food security; Dairy farmers; Good agricultural practices (GAPs)